Aging in the intellectually and developmentally delayed community: comorbid I/DD + dementia - Lake, Jeanne Squires (Kansas State University, 2019)
Humankind gains of greater longevity increase greater numbers of aging people worldwide, including those with Intellectual and Developmental Disorders (I/DD) (Alvarez, 2015). When an I/DD is present in an individual, and age-related disease (such as dementia) is also diagnosed, it is often referred to as a comorbid diagnosis. Comorbid diagnosis simply means that there is more than a single disease or condition present in one body at the same time. Diagnosis of a comorbid I/DD + dementia can be complicated and needs to be based on previously existing levels of cognitive disabilities in the individual with I/DD. Establishing an individualized record of peak performance baseline functioning at age 25-35 builds a threshold for measuring future age-related decline in these individuals with I/DD. Baseline function can differentiate if a newly appearing symptom in an individual with I/DD is a normal aging associated process, or a disease-related-decline. Through a literature review, informed by research based scholarship, program based publications, and professional sources (including professional websites) on topics of normal aging, I/DD, AD and dementia, this project will 1) describe prevalence/incidence studies of comorbid I/DD + dementia diagnosis in locations around the world, including challenges and conflicts of the research, 2) explore non-disease-related, age-associated patterns common in the I/DD community, 3) examine common indications of disease-related cognitive decline of individuals with I/DD + dementia, 4) discuss support frameworks available for comorbid (I/DD + dementia) individuals and caregivers, 5) suggest where to look for support networks that can assist caregivers and family members, post-diagnosis, in best practices for the comorbid individual, and themselves, as caregivers.
Keywords: Aging; Dementia; Intellectually disabled; Developmentally delayed